XML-Driven batch upload of input files under the enhanced examination online - Orcasitas, Charlene Nina H. (2010)
The Enhanced Examination Online (EEOL) is an effective system for creation and management of examinations. One of the features of the EEOL is the batch uploading of questions. The teachers could batch upload a file which is in XML format. With batch uploading, the manual or one by one input is eliminated. For each XML, the file that a teacher creates, he/she could input multiple question items. However, this functionality of EEOL must be maximized in order to achieve the system?s efficiency. This study aimed to further expand the batch uploading feature of EEOL. Using a teacher?s account, the batch uploading of questions was categorized into three levels. For level 1, the Teacher could directly batch upload the question file thus no subject was selected from the Subjects tab. For level 2, the Teacher should select a subject from the list of subject assignments but there is no chapter selection. For level 3, the Teacher could batch upload the question file by selecting first the subject and then followed by selecting the chapter number. New options for batch upload were added on the respective levels of organizing chapters and questions. So that for every level, the Teacher could batch a question. Aside from question files, this study could also batch upload student lists and class lists using the Administrators account. The batch upload of class list was also categorized into two levels, where level 1 has no subject offering selected and level 2 has a selected subject offering. New options were added for batch upload in the student and class accounts management. As a result, adding new student accounts, new set of class list for a particular class and questions per examination were done easier through batch uploading XML files and made the batch upload features maximized its functionality
Thesis (BS Computer Science) -- University of the Philippines Mindanao, 2010
Keywords: Batch upload; Xerces java parser; XML